The Potential of Liquid Tofu Waste in Increasing Antioxidant Activity of Robusta Green Coffee - Sulistyaningtyas, Ayu Rahmawati; Wilson, Wildiani (Biosaintifika: Journal of Biology & Biology Education, 2018)
Robusta is the most widely cultivated coffee in Indonesia (90% of the total Indonesian coffee production). Antioxidant activity and polyphenol content of Robusta coffee is higher than Arabica coffee or the other plants. One of the efforts, for coffee market expansion is product diversification through decaffeination of coffee . Decaffeination is one of process to reduce caffeine content. Decaffeinated coffee (decaff coffee) began to become public demand. In addition to its more delicious taste, low caffeine coffee is beneficial for health because it is safer to eat. Coffee decaffeination can utilize organic solvents that contain proteases. Tofu waste was one of protease sources. So that, tofu waste had potential as solvent in decaffeination The objective of the study was to assess the antioxidant activity of Robusta green coffee after going through decaffeination by using tofu waste. The study was used Factorial Completely Randomized Design, i.e . concentration of tofu waste (30%,60%, 90%) and length of immersion (3, 6, 9 hours). Robusta green coffee antioxidant activity was examined by using DPPH method. The results showed that the highest antioxidant activity ( 17.6061) was in the treatment of 90% waste concentration and 9 hours of decaffeination time. In conclusion, the greater the concentration and the longer the decaffeination resulted in the higher antioxidant activity. This study provides information about coffee processing methods that can produce coffee with the best quality. So, It can increasing the value of domestic coffee products especially in the global market and utilizing tofu liquid waste to be more malleable.